THE SILENT BONE THIEF: A 60-YEAR-OLD MAN'S JOURNEY FROM CHRONIC BACKACHE TO A DIAGNOSIS OF MULTIPLE MYELOMA (Asian Journal of Medical Research and Health Sciences, 2026)
Multiple myeloma (MM) is a malignant plasma cell neoplasm that remains notoriously difficult to diagnose at its earliest stages, often masquerading as benign musculoskeletal or haematological conditions. We report the case of a 60-year-old male shopkeeper who presented with a six-month history of insidious back pain and progressive generalised weakness. A systematic workup revealed markedly elevated total protein with grossly inverted albumin-to-globulin ratio, normocytic normochromic anaemia, renal impairment, elevated inflammatory markers, and on serum protein electrophoresis — an M-band (3.9 g/dL) in the gamma globulin region with elevated kappa light chains. Peripheral blood smear showed normocytic normochromic red cells. Bone marrow aspirate imprint smear demonstrated numerous plasma cells, flame cells, binucleated forms and plasmablasts. Bone marrow trephine biopsy confirmed plasma cell neoplasm — multiple myeloma. Radiological imaging demonstrated extensive lytic bone lesions and vertebral osteoporosis. The case illustrates the diagnostic odyssey inherent to MM and underscores the critical importance of a thorough workup in an elderly male presenting with back pain and anaemia.